Relationships between body fat depots, carcass composition, live weight and body condition scores in Blanca Celtibérica goats - Delfa R.; González C.; Teixeira A.; Gosalvez L.F.; Tor M. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
The relationships between body fat depots, carcass composition and body condition scores (BCS), assessed on lumbar, sternal and tail regions were determined in 19 adult Blanca Celtibérica goats. After slaughter the omental, mesenteric, kidney and pelvic fat were separated and weighted. The left side of the carcass was separated into muscle, bone plus remainder, subcutaneous and intermuscular fat. All body fat depots and carcass composition tissues have a logarithmic or semilogarithmic relationship with body condition scores. All body condition scores assessed on lumbar and sternal regions were better predictors than live weight (LW) of the body fat depots and carcass composition. The body condition score assessed on the sternal region was a better predictor than the other body condition methods for all fat depots and carcass composition except for the heart and pelvic fat. The variations in omental, mesenteric, subcutaneous, intermuscular, pelvic and kidney weight of fat depots per unit change in sternal body condition score (SBCS) were determined. These changes suggest that the increases in SBCS from 2.5 to 3.5 or from 3.5 to 4.5 result in the greatest rate of deposition occurring in the subcutaneous and omental fat depots.
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)